PENINGKATAN MUTU MADRASAH IBTIDAIYAH: SCHOOL-BASED MANAGEMENT DAN KOMPETENSI GURU MADRASAH - Nuryanto Nuryanto (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
Madrasah Ibtidaiyah (MI) is an Islamic elementary educational institution that has a certain distinction compared to general elementary education known as Sekolah Dasar (SD). The difference of MI, as a leading elementary school that not only develop general knowledge but also build Islamic character, places it in a very strategic position to build young generation’s character since their early ages. Unfortunately, it is widely found in Indonesia that there are still many MIs that have no good quality of education yet. This condition leads to the fact that the people’s preference goes more to SD than MI. This article attempts to give brief elaboration school-based management and teachers’ competence as the strategies to increase the quality of education in MI so that it becomes the society’s choices.